From Motives to Actions: A Study of Citizen Engagement in Health and Human Service Contracts. Issue 3 (17th February 2021) - Amirkhanyan, Anna; Lambright, Kristina; Islam, Shahriar
ABSTRACT: Analyzing data from 93 semi-structured interviews, this paper identifies common forms of citizen participation, motives driving these efforts, uses of feedback, and engagement challenges. It also explores interrelationships among these aspects of participation. The findings suggest that organizations with more motives for engagement offered a wider array of opportunities for participation and used the input in more ways. In addition, organizations more active in engaging citizens and using feedback were more likely to experience challenges. This study highlights the complexity of public participation and encourages public and private managers to be informed about its many benefits and barriers.